Application of interactive and graphic systems for higway location and route selection - Catbagan, Jerome L. (2001)
Computer-assisted systems are fast becoming more of a necessity than just an expensive option. The price of acquiring such systems, although quite high, may often be offset by increases in productivity and reduction in work time, thus gaining significant net savings in the long run. This study presents and evaluates a technique in highway location and route selection that uses interactive and graphic systems. A system was developed that would provide a means for efficient drawing conversion and data manipulation. Hand-drawn alignment sketches on maps were easily converted into vector drawings and all alignment coordinate and element data were stored in a data bank. Also included in the system was the evaluation module for the generated vector representation of alignments. The concept of cost models was used for the evaluation procedures, where three-dimensional cost representations of the surrounding environs of the alignment were depicted. From these models, the total alignment costs may be calculated, which may be then used as a basis for selecting the best route. The system was found to be effective in evaluating and comparing results given different alignments schemes, based on the two tests cases presented.